lPv6 Transition: Why A New Security Mechanisms Model Is Necessary. - Hj Mat Taib, Abidah; Budiarto, Rahmat; Samsudin, Azman (2007)
This paper describes the scenario in the transition oflpv4 to lpv6 with focusing on the security issues involved in each of the transition methods: dual stack and tunneling. Then, the paper analyze the existing security mechanisms available and identify new considerations for a new security model.